You can't go home again: Changes in trophic niche following extinction and recolonization of the New Zealand sea lion - L. C. Wing; S. R. Wing; R. Kinaston; A. J. M. Sabadel; I. Smith (Ecosphere)
Abstract Recolonization or range expansion of large marine predators can be facilitated by reestablishing formally important trophic linkages within intact coastal marine food webs. We analyzed long‐term changes in the structure of coastal marine food webs supporting remnant and recolonizing populations of New Zealand sea lions (Phocarctos hookeri), an apex marine predator, using trophic position and mixture of alternate sources of organic matter as metrics for their resource niche. We measured δ13C, δ15N, and δ15NAA of amino acids in collagen of archived prehistoric bone samples and modern bone, muscle, and fur samples. Using the resulting isotopic values, we calculated individual‐based estimates of trophic position and basal organic matter source use from pelagic and benthic habitats, phytoplankton versus macroalgae, in the underlying food webs supporting sea lions from the Auckland Islands, Stewart Island, Southland, and Otago among discrete time periods dating to the first human settlements in New Zealand. The data resolved significant changes in trophic position of New Zealand sea lions since the first arrivals of Māori in New Zealand (ca. 1250–1450 CE), the advent of European whaling and sealing (ca. 1650–1850 CE), when sea lions were extirpated from the South Island, and expansion of industrialized fishing (ca. 1950 to present CE) indicating a vastly altered resource landscape for recolonizing populations on the South Island. New Zealand is the last major land mass to be settled by people; therefore, the patterns we observe comprise the complete time course of human influences on the marine ecosystem. These patterns provide a unique understanding of how long‐term changes in coastal marine food webs influence the trophic position and population recovery of apex predators.